Molecular causes of a complex disease with high prevalence in Black South Africans (non-insulin dependent diabetes mellitus) and a rarer heterogeneous monogenic disease (hypertrophic cardiomyopathy) - Ngumbela, K. C (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1999.